Budaya Migrasi Dan Kearifan Lokal Masyarakat Suku Bajo Dalam Mengelola Sumber Daya Alam Yang Berkelanjutan - Muhammad Agus Umar (Peneliti.net, 2019)
The problem of population in Indonesia essentially involves three aspects, namely the aspect of quantity, aspects of quality and aspects of mobility (migration). Migration is the movement of the population with the aim of settling from somewhere else. This study aims to examine the culture of migration and local wisdom of the Bajo people which are related to sustainable use of natural resources. The method used is literature review. In the discussion, information was obtained that dependence on marine natural resources caused the people of the Bajo to move from one area to another with the aim of obtaining sources of life from the sea. To preserve marine natural resources, the Bajo tribe has a concept of local wisdom called pamali.